The Belt and Road Initiative and Partnership for Global Infrastructure and Investment: Comparison and current status - Mykyta Simonov (Asia and the Global Economy, 2025)
The last decade has witnessed the development and implementation of two major infrastructure initiatives: China’s Belt and Road Initiative (BRI) and the Partnership for Global Infrastructure and Investment (PGII) by the United States and the G7 countries. The escalating political confrontation between China and the United States made these initiatives crucial for strengthening their geopolitical positions and economic dominance. This paper examines the impact of BRI on competitive strategies of the United States and its partners in response to China’s growing influence, thereby enhancing the understanding of contemporary political and economic dynamics. Key factors supporting the thesis of increasing competition and confrontation are considered, demonstrating that U.S. leadership leverages its infrastructure initiatives to oppose and constrain China’s influence at both the foreign policy and economic levels. Our analysis identifies factors directly influencing the development of these initiatives and compares the principles of BRI and PGII to objectively evaluate their effectiveness.